Use of dBase IV and dBase/SQL for Information Processing and Retrieval in Libraries - Paul Pandian, M. (Journal of Information and Knowledge, 1991)
Discusses the features of dBase/SQL. Identifies the factors that help information retrieval. Privides format for entry details for bibliographic database. Illustrates search query formats using dBase/SQL.